(untitled) (ModaPalavra e-periódico, 2020)
To broaden their cultural influence, gain new consumers or retain current loyalty (target), luxury brand managers also diversify products and marketing strategies. An example of this is the launch of the Canvas of the Future bag, a Louis Vuitton brand prod uct that boasts digital technology capabilities, integrating the idea of technological innovation with luxury brand and product concepts. Thus, we sought to describe and interpret the perception of Fashion experts about the product, conducting a descript ive - qualitative research, whose epistemological basis is Phenomenology. In summary, four research steps were considered and developed to: 1) explore; 2) collect; 3) relate information, and 4) raise propositions. Among the results of the study, we highlight considerations such as: pioneering, innovative, surreal and futuristic regarding the product, confirming the contemporary hybridism between the tradition of fashion and technological innovation, highlighting the revision and repositioning of the brand and the product of Lux.